Students experiences of an 8-week mindfulness-based intervention at a college of opportunity: a qualitative investigation of the mindfulness-based college program - William R. Nardi; Nour Elshabassi; Jayson Spas; Alex Zima; Frances Saadeh; Eric B. Loucks (BMC, 2022)
Abstract Background Mindfulness-based programs have the potential to improve the well-being of undergraduate students by reducing anxiety, depression, and isolation in the wake of the COVID-19 pandemic. The aim of this qualitative study was to explore lived experiences of undergraduates in a mindfulness-based program at a "college of opportunity" that has high proportions of first-generation college students. Specifically, we sought to: (1) explore the application of mindfulness practices in students' daily lives; (2) explore how participants believe mindfulness training affected their health and well-being; (3) learn participants' recommendations and suggested changes for mindfulness-based interventions in future iterations. Methods Students were recruited from XXX and consented to participate in semi-structured digitally conducting interviews after the completion of the 8-week intervention in the Fall/Spring 2020 academic year. Data were analyzed using Applied Thematic Analysis and a codebook was constructed using a consensus-driven process using both a priori and emergent coding. All transcripts were double-coded, and concordance was achieved for all interviews. Results Qualitative results indicated that the most applied practices were those that could be easily incorporated into a daily routine. Furthermore, students reported an increased ability to cope with a variety of stressors, decreased reactivity, and enhanced resilience specifically concerning mental health challenges. Additionally, engaging in mindfulness training improved students' ability to navigate social distancing measures, other COVID-19-specific stress, and enhanced motivation for self-care practices to sustain well-being. Concerning preferred intervention delivery modality, participants stated that due to multiple, growing responsibilities (e.g., pressures of commuting to class) they preferred in-person delivery, shorter sessions over a longer period, with classes in the morning or early afternoon. Conclusions Findings provide pragmatic and psychosocial insights into students' application of mindfulness training across personal, professional, and academic domains enhancing their well-being. This work builds on qualitative work concerning students' perceptions and applications of mindfulness while offering insights into the future of mindfulness programs among undergraduates. Trial registration Clinicaltrials.gov NCT03124446.